2008
DOI: 10.1055/s-2008-1038350
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years after the Initiation of Congenital Heart Surgery in Guatemala: Observations after a One Year Fellowship in the Pediatric Cardiac Unit in a Low Income Country

Abstract: High-tech medicine in a low income country remains a controversial issue. In September 1997, a congenital heart surgery program was initiated in Guatemala by Aldo Castañeda, emeritus Harvard Professor of Surgery and surgeon-in-chief at the Children's Hospital Boston. He trained 3 young pediatric cardiac surgeons and in addition assembled a team of pediatric cardiologists, intensivists, anesthesiologists, nurses and the necessary technical staff to develop a pediatric cardiac program in Guatemala. Faced with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Often, well-meaning programs or missions from HICs will prioritize the performance and education of their own trainees and surgeons, without investigating or addressing the surgical needs of the LMIC. 2 Our findings lend credence to this claim: 13 of the 18 articles on Northto-South exchanges reported on the operative numbers and performance of HIC trainees, 15,[17][18][19][20][21]23,24,26,27,[30][31][32] whereas only 2 of these programs stated that they educated and evaluated surgical trainees from the host LMIC. 18,21 This indicates a large area for potential improvement, as training LMIC surgeons in their home countries is a wellestablished way to address the surgical workforce gap.…”
Section: E559mentioning
confidence: 61%
See 1 more Smart Citation
“…Often, well-meaning programs or missions from HICs will prioritize the performance and education of their own trainees and surgeons, without investigating or addressing the surgical needs of the LMIC. 2 Our findings lend credence to this claim: 13 of the 18 articles on Northto-South exchanges reported on the operative numbers and performance of HIC trainees, 15,[17][18][19][20][21]23,24,26,27,[30][31][32] whereas only 2 of these programs stated that they educated and evaluated surgical trainees from the host LMIC. 18,21 This indicates a large area for potential improvement, as training LMIC surgeons in their home countries is a wellestablished way to address the surgical workforce gap.…”
Section: E559mentioning
confidence: 61%
“…Many articles in our review reported primarily on the number of operations performed by trainees or on surveys of trainees' impressions of the exchange program. Although 9 of the 28 studies reported that trainees or their programs had produced research, 14,18,27,28,[31][32][33]36,37 and 4 reported on the current practice status of former trainees, 33,[36][37][38] none reported on the clinical outcomes of the patients treated during the exchange or the overall impact on the surgical disease burden in the area visited. Our review indicates that current authors are doing little to report on the value or impact of exchanges beyond the direct effect on trainees.…”
Section: E559mentioning
confidence: 99%
“…In addition, the case profiles of training institutions in high-income countries are often quite different from LMICs and may not prepare the prospective trainee for the specific challenges faced later in his or her career. [ 6 ] Notwithstanding all the exposure under supervision, acquisition of skills required for consistently safe newborn and infant surgery takes considerable additional time. This process is reflected in the long learning curve that is often visible even after becoming an independent surgeon.…”
Section: What Are the Barriers?mentioning
confidence: 99%
“…The Guatemalan program of Pediatric Cardiac Surgery was initiated in January 1997. Initially, we aimed our efforts toward repair of less complex congenital cardiac malformations beyond the neonatal age in Risk Adjustment for Congenital Heart Surgery (RACHS-1) 7 9 categories 1, 2, and 3. After 1999, we began to also accept neonates and young infants with complex lesions, including TGA.…”
Section: Introductionmentioning
confidence: 99%